The Effect of Digital-Based Nutrition Education on the Pattern of Complementary Feeding in Infants - Rochmanita Sandya Afindaningrum; Luh Mertasari; Nofita Setiorini Futri Purwanto; Sony Bernike Magdalena Sitorus; Nur Sri Atik (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Improper complementary feeding (MP-ASI) is still a nutritional problem in infants, influenced by lack of maternal knowledge and limited access to effective education. The use of digital media has the potential to increase the understanding of mothers in a more flexible and sustainable manner. This study aims to analyze the effect of digital-based nutrition education on patterns of complementary feeding in infants. The study used a quantitative design with a type of quasi-experimental one group pretest-posttest. The location of the study in Posyandu Kelurahan Anduring, Padang, with a sample of 45 mothers who have babies aged 6-12 months, was selected using purposive sampling technique. Data were collected through structured questionnaires and observation of complementary feeding practices before and after the digital education intervention. Data analysis was conducted univariate to see the frequency distribution and bivariate using paired t-test. The univariate results showed an increase in maternal knowledge scores from an average of 62.4 to 82.7 and good complementary feeding practices increased from 40% to 75.6%. Bivariate analysis showed that there is a significant effect of digital education on knowledge (p=0.001) and practice of complementary feeding (p=0.002). It was concluded that digital-based nutrition education is effective in improving the knowledge and practice of mothers in providing complementary feeding. The implication of this study is the need for the integration of digital education programs in posyandu activities as a preventive promotive strategy to improve the quality of MP-ASI delivery in a sustainable manner.